Vaccine Development in the Time of COVID-19: The Relevance of the Risklick AI to Assist in Risk Assessment and Optimize Performance - Haas, Quentin; Borisov, Nikolay; Alvarez, David Vicente; Ferdowsi, Sohrab; von Meyenn, Leonhard; Teodoro, Douglas; Amini, Poorya (Frontiers in Digital Health, 2021)
The COVID-19 pandemic revealed the urgent need for acceleration of vaccine development worldwide. Rapid vaccine development poses numerous risks for each category of vaccine technology. Using Risklick AI, we estimated risks associated with all types of COVID-19 vaccine during the early phase of vaccine development. We then performed a post-mortem analysis of the probability and impact matrix calculation by comparing the 2020 prognosis to the contemporary situation. We used Risklick AI to evaluate the risks and their incidence associated with vaccine development in the early stage of the COVID-19 pandemic. Our analysis revealed the diversity of risks among vaccine technologies currently used by pharmaceutical companies providing vaccines. This analysis highlighted current and future potential pitfalls connected to vaccine production during the COVID-19 pandemic. Hence, the Risklick AI tool appears as essential in the future of treatment development, in order to formally anticipate risks and increase overall performance from production to distribution of vaccines. Risklick AI could therefore be extended to other fields of research and development and represent a novel opportunity in the calculation of production-associated risks